Economic Reform in New Zealand 1984-95: The Pursuit of Efficiency - Evans, Lewis; Grimes, Arthur; Wilkinson, Bryce (Journal of Economic Literature, 1996)
Between 1984 and 1995 New Zealand changed from a closed and centrally controlled economy to one of the most open countries in the OECD. The reforms liberalizing the economy were notable for their very comprehensive coverage and innovations that included: performance contracts for senior civil servants and the central bank, legislated constraints on fiscal expenditure decisions backed by accrual accounting, tax neutrality, subsidy-free agriculture, and no industry-specific regulation of competition. Modern microeconomics contributed much to policy design. Economic growth has been vigorous since 1991, but a different sequencing of reforms may have enhanced outcomes.